Delayed Ego Strength Development in Opioid Dependent Adolescents and Young Adults. (17th November 2015) - Abramoff, Benjamin A.; Lange, Hannah L. H.; Matson, Steven C.; Cottrill, Casey B.; Bridge, Jeffrey A.; Abdel-Rasoul, Mahmoud; Bonny, Andrea E.
Abstract : Objective . To evaluate ego strengths, in the context of Erikson's framework, among adolescents and young adults diagnosed with opioid dependence as compared to non-drug using youth. Methods . Opioid dependent (n = 51 ) and non-drug using control (n = 31 ) youth completed the self-administered Psychosocial Inventory of Ego Strengths (PIES). The PIES assesses development in the framework of Erikson's ego strength stages. Multivariate linear regression modeling assessed the independent association of the primary covariate (opioid dependent versus control) as well as potential confounding variables (e.g., psychiatric comorbidities, intelligence) with total PIES score. Results . Mean total PIES score was significantly lower in opioid dependent youth (231.65 ± 30.39 opioid dependent versus270.67 ± 30.06 control;p < 0.01 ). Evaluation of the PIES subscores found significant (p < 0.05 ) delays in all ego strength areas (hope, will, purpose, competence, fidelity, love, care, and wisdom). When adjusting for potential confounders, opioid dependence remained a significant (p < 0.001 ) independent predictor of total PIES score. Conclusion . Adolescents with opioid dependence demonstrated significant delays in ego strength development. A treatment approach acknowledging this delay may be needed in the counseling and treatment of adolescents with opioid dependence.